The impacts of multiple lightshelves on natural lighting distribution and effective temperature at office rooms - Indarto, Eddy; Hardiman, Gagoek; Budi, Wahyu Setia; Riyanto, Djalal Er (Journal of Architecture and Urbanism, 2017)
Daylighting with light-shelf is not a simple strategy. Therefore, this research aims to investigate how far the application of light-shelf can block direct sunlight and how much the distribution of daylight at office rooms is produced.This research is a simulation using EnergyPlus from OpenStudio. Data as measurement results collected from on-site research were used as the validation base of the simulations both with multiple light shelves and without multiple light shelves.The building orientation is toward north east (azimuth 51°), and the result showed that using multiple light shelves on the building was able to distribute evenly the intensity of natural lighting into the rooms. On the edge of the windows, there has been change of the light intensity which was previously too bright (from 925 Lux at 5 p.m. for the lowest and 7200 Lux at 9 a.m. for the highest; to 460 Lux at 5 p.m. for the lowest and 1400 Lux at 12.00 p.m. for the highest). Besides, the use of multiple light shelves was also able to lower the room temperature particularly at rush hours starting from 9.00 a.m. to 3.00 p.m. where the biggest difference of the temperature occurred at 3.00 p.m. (between 29.1 °C and 28.4 °C in which the temperature decreased 0.7 °C). These aforementioned facts have given contribution to the efficiency of energy used in AC while the main benefit of this research is developing knowledge about daylighting in architectural design particularly in passive design method.